Investigation of thermal decomposition of polymer nanocomposites with different char residues. (29th April 2015) - Ren, Xiaonan; Zong, Ruowen; Hu, Yuan; Lo, Siuming; Stec, Anna A.; Hull, Terence Richard
<x xml:space="preserve">Abstract</x> The pyrolysis process of polypropylene (PP), PP‐based nanoclay composites, acrylonitrile‐butadiene‐styrene (ABS), and ABS/metal hydroxide nanorods (MHR)/grapheme nanosheets (GNS) composites in a cone calorimeter test was simulated with a recently developed numerical codes, the Federal Aviation Administration ThermaKin. First, the heat release rate (HRR) and the surface temperature as a function of time were compared with experiment data. With reasonable input parameters, the pyrolysis behaviors were predicted reasonably. Subsequently, the influence of the properties of char residue on the HRR was discussed. The char residue of PP/nanoclay acted as a heat transfer barrier, while the char layer of ABS/MHR/GNS acted as a mass transfer barrier. Finally, the sensitivity of the residue characteristic parameters to the model output was discussed. Copyright © 2015 John Wiley & Sons, Ltd.